2011
DOI: 10.1002/cbf.1820
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of intracellular and extracellular α‐glucosidases from Geobacillus toebii strain E134

Abstract: Two different α-glucosidase-producing thermophilic E134 strains were isolated from a hot spring in Kozakli, Turkey. Based on the phenotypic, phylogenetic and chemotaxonomic evidence, the strain was proposed to be a species of G. toebii. Its thermostable exo-α-1,4-glucosidases also were characterized and compared, which were purified from the intracellular and extracellular fractions with estimated molecular weights of 65 and 45 kDa. The intracellular and extracellular α-glucosidases showed optimal activity at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…The results obtained for corn α-glucosidase were in correlation with the previous reports. Most of α-glucosidases have an optimum temperature between 35-65ºC [7,14,33,36,37]. Similar results have been reported by Iwata et al [6].…”
Section: Effect Of Temperature On Enzyme Activity and Stabilitysupporting
confidence: 70%
See 2 more Smart Citations
“…The results obtained for corn α-glucosidase were in correlation with the previous reports. Most of α-glucosidases have an optimum temperature between 35-65ºC [7,14,33,36,37]. Similar results have been reported by Iwata et al [6].…”
Section: Effect Of Temperature On Enzyme Activity and Stabilitysupporting
confidence: 70%
“…Various temperature-stability results of α-glucosidases have been obtained depending the source of enzyme, temperature, incubation time and reaction conditions. Cihan et al [37] have found that both intracellular and extracellular α-glucosidases from G. toebii strain were very stable between temperature ranges of 35-70ºC. Marin et al [38] have also found that α-glucosidase from X. dendrorhous was very stable to thermal treatment up to 50ºC.…”
Section: Effect Of Temperature On Enzyme Activity and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the optimum temperature for α-glucosidase activity of the r Aci HBGase II-(His) 6 enzyme was at 45°C (with 80–90% residual activity at 40–55°C), which is much higher than that previously reported by Wu et al [32], and higher than the physiological temperature of the bees. However, within extreme thermophiles, Nashiru et al [33] reported a novel HBGase from Thermus caldophilus GK24 with an optimal temperature of 90°C, whilst the intracellular and extracellular HBGases from G. toebii strain E134 showed an optimum activity of 65°C and 70°C, respectively [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Industrial application of these enzymes requires stability at high temperatures as well as toward common denaturant agents, and therefore, enzymes isolated from thermophiles have gained attention over the past decade [ 7 ]. There are many thermostable α-glucosidases from different thermophilic and hyperthermophilic microorganisms such as Sulfolobus tokodaii [ 7 ], Geobacillus toebii [ 19 ], Thermus caldophilus [ 20 ], Thermoplasma acidophilum [ 21 ], Bacillus stearothermophilus [ 22 ] and Thermus thermophilus [ 23 , 24 ] have been discovered and characterized, and several mesophilic α-glucosidases have been engineered by mutagenesis to enhance enzyme thermostability [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%